Disruption Management Amidst Covid-19 Pandemic Crisis of Businesses in Cotabato City - Mary Ann R. Pasaje DBM; Joseph A. CastillonMBA; Josefina M. Mejos MBA; Catlyn O. Pongot, DBA (Educational Administration: Theory and Practice, 2024)
Disruption Management is critical for the survival and sustainability of a company, especially during a pandemic. Recognizing business challenges would mean that the business could identify business opportunities that may provide a new perspective on income-generating activities for the business. The study’s objective is to explore the local businesses’ experiences in disruption management amidst this covid-19 pandemic which greatly affected almost all types of business. Ten key informants came from different business types offering products and services in the area. The researchers employed purely qualitative method in accomplishing this research study. The thoughts and shared experiences of the participants on the topic at hand brought tremendous knowledge to the researchers. Though key informants represent different business types, they shared very similar experiences with the challenges mentioned in the literature of the studyThe most common challenges the local business encountered were financial difficulty and impeding business transactions. In contrast, the most common opportunities included the shift in daily social activities and changes in consumption patterns. The most typical approaches to managing disruption were altering how the business performs, creating strategic alliances, digitalizing business transactions and distant operations, and employing flexible and sustainable schemes